HIPK2 Overexpression and Its Prognostic Role in Human Papillomavirus-Positive Tonsillar Squamous Cell Carcinoma - Kwon, Mi Jung (Biomed Res Int, 2017)
Tonsillar squamous cell carcinomas (TSCCs) are the most common human papillomavirus- (HPV-) associated oropharyngeal cancers with poor prognosis. Homeodomain-interacting protein kinase 2 (HIPK2) is a central regulator of p53, which participates in apoptosis during the DNA damage response. HIPK2 is involved in HPV-associated uterine cervical and cutaneous carcinogenesis through its binding of HPV E6, thereby preventing apoptosis and contributing to tumor progression. However, its clinical and prognostic significance in TSCC remains unclear. HIPK2 mRNA levels were analyzed in 20 normal tonsils and 20 TSCC specimens using real-time reverse transcription polymerase chain reaction. Immunohistochemistry of HIPK2 was performed in 79 resected specimens. HIPK2 was expressed in 57% of the TSCCs, and HIPK2 protein expression and HIPK2 mRNA levels were higher in TSCCs than in normal tonsils. HIPK2 overexpression was associated with poorly differentiated carcinoma and low alcohol consumption and was an independent prognostic factor for overall survival and disease-free survival (DFS) in TSCC and a negative independent prognostic factor for DFS in patients receiving postoperative radiotherapy. HIPK2 overexpression had a significant association with poorer DFS in HPV-positive TSCCs, but not in HPV-negative tumors. HIPK2 overexpression may be a potential prognostic marker for predicting prognoses and a high risk of recurrence, particularly in patients with HPV-positive TSCC.